2014
DOI: 10.1038/srep05397
|View full text |Cite
|
Sign up to set email alerts
|

Green strategy from waste to value-added-chemical production: efficient biosynthesis of 6-hydroxy-3-succinoyl-pyridine by an engineered biocatalyst

Abstract: Value-added intermediates produced by microorganisms during the catabolism of N-heterocycles are potential building blocks for agrochemical synthesis and pharmaceutical production. 6-Hydroxy-3-succinoyl-pyridine (HSP), an intermediate in nicotine degradation, is an important precursor for the synthesis of drugs and compounds with biological activities. In the present study, we show that an engineered biocatalyst, Pseudomonas putida P-HSP, efficiently produced HSP from the renewable raw material of tobacco-wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 41 publications
2
31
0
Order By: Relevance
“…Another strategy used may involve the inhibition of metabolic pathways to increase the production of the desired compound by a modified strain. Yu et al (2014) genetically constructed the strain P. putida P-HSP to accumulate 6-hydroxy-3-succinoyl-pyridine, an intermediate in nicotine degradation, by blocking the catabolic pathway of nicotine. Homologous recombination was used to disrupt the hspB gene in strain, P. putida S16, which is necessary to convert 6-hydroxy-3-succinoyl-pyridine into 2,5-dihydroxy-pyridine.…”
Section: Improving Microorganismsmentioning
confidence: 99%
“…Another strategy used may involve the inhibition of metabolic pathways to increase the production of the desired compound by a modified strain. Yu et al (2014) genetically constructed the strain P. putida P-HSP to accumulate 6-hydroxy-3-succinoyl-pyridine, an intermediate in nicotine degradation, by blocking the catabolic pathway of nicotine. Homologous recombination was used to disrupt the hspB gene in strain, P. putida S16, which is necessary to convert 6-hydroxy-3-succinoyl-pyridine into 2,5-dihydroxy-pyridine.…”
Section: Improving Microorganismsmentioning
confidence: 99%
“…Nicotine could potentially be used for the production of value-added chemicals. 6-Hydroxy-3-succinoylpyridine (HSP), an important precursor for the synthesis of compounds with biological activities, was efficiently produced by an engineered nicotine-degrading strain (5). Therefore, the study of the mechanism of nicotine degradation provides useful information for both bioremediation and biocatalysis.…”
mentioning
confidence: 99%
“…6HN can potentially serve as a precursor for the synthesis of a neonicotinoid. In contrast, the formation of 2-substituted pyridine derivatives requires strict conditions for high product yields in organic chemistry methods (26). This study, therefore, not only extends the understanding of molybdenum-containing hydroxylases but also provides a useful potential biocatalyst preparation for nicotine biotransformation.…”
Section: Discussionmentioning
confidence: 88%
“…Microbial degradation of pyridine derivatives, such as nicotine, may produce numerous useful intermediates for agrochemical and pharmaceutical synthesis (26). Here, we demonstrated that the recombinant strain P. putida KTVppA is an efficient biocatalyst for the biotransformation of nicotine to 6HN, which can easily be modified by replacing the hydroxide radical with a halogen element.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation